Pengaruh Tingkat Pengangguran Terbuka, Tingkat Pendidikan, Upah Minimum Kerja dan Indeks Pembangunan Manusia Terhadap Jumlah Penduduk Miskin di Provinsi Lampung - Nurmala Sari; Leony Octaviani Yusuf; Rangga Andhika; Nur Ihsan; Muhammad Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Poverty is one of the fundamental problems that is of concern to the central government in any country, nationally and internationally. Indonesia is one of the countries that is still trapped in the problem of poverty which has not yet been completely resolved. This research aims to analyze the influence of open unemployment, government expenditure, human development index on the number of poor in Lampung Province. The research data used is secondary data from publications by the Lampung Province Central Statistics Agency. The independent variables in this research are the influence of Open Unemployment and the Human Development Index, while the dependent variable is the Number of Poor People. The analysis technique used is Multiple Regression Analysis with the Ordinary Least Square (OLS) Method. The research results show that Open Unemployment (TPT) research has a negative and insignificant effect on the number of poor people, education level (TP) has a negative and not significant effect on the number of poor people, the minimum wage (UMK) has a significant positive effect on the number of poor people, while the Human Development Index (HDI) has an insignificant negative effect on the number of poor people. The results of the F test, Open Unemployment, Government Expenditures and the Human Development Index have a simultaneous or equally significant positive effect on the Number of Poor People in Lampung Province.